Prophetic wisdom: engaged Buddhism's struggle for social justice and complete liberation - Strain, Charles R. (SUNY series in religious studies, 2024)
"Shows how Engaged Buddhists can expand their understanding of the causes of collective suffering and develop nonviolent means for social transformation through a dialectic of love, power, and justice"--